Patient’s Perceptions and Experiences about the Root Canal Treatment: A Survey among Patients Visiting Nobel Medical College - Singh, Amit Kumar; Chamlagain, Alisha (Nepal Journal of Health Sciences, 2024)
Introduction: One major drawback of root canal therapy (RCT) is that most people don't know enough about it. To effectively address the issue, it is imperative to comprehend and identify the elements that impede or discourage patients from undergoing Root Canal Treatment. A survey of the literature reveals a dearth of information regarding patients' understanding and acceptability of root canal treatment (RCT) in the Nepali community.Objective: The objective of the study was to determine how well-informed patients were about root canal treatment at Nobel Medical College and Teaching Hospital in Biratnagar. A wide-ranging patient viewpoint on the matter was sought by means of a patient survey.Methods: This survey was conducted with the help of prestructured questionnaire consisting of 15 questions, distributed to random 250 patients coming to the outpatient department of Conservative dentistry and Endodontics at Nobel Medical College and Teaching Hospital. The completed questionnaires were then analyzed to assess patients’ experiences, concerns, and perceptions about RCT. Results: There is a lack of awareness among patients regarding RCT. Conclusion: The people need to be made more aware of the importance of maintaining a healthy dentition and the consequences that follow if this isn't done. If patients were fully informed about endodontic procedures, more might consider having them.